THE SPECTRAL VARIATIONS OF VY MON IN 1986-1992 - Pavlova, L. A. (Одеські астрономічні публікації, 2017)
The variations of the 3-component profiles of the spectrum of VY Mon are reported which may be explained by restricted models of variable anisotropic stellar wind.